Hedonic adaptation in cultural consumption: evidence from China Family Panel Studies - Yuan He; Liangbo Zhang; Chi Zhang; Zhimin Zhou (Humanities & Social Sciences Communications)
Abstract Understanding the impact of cultural consumption on well-being has both economic and policy implications, offering valuable insights for theory and practice. Most researchers have identified linear relationships between these concepts, but few have explored the nonlinear relationship. This study utilizes household economic data and draws on the China Family Panel Studies (CFPS) database from 2010, 2014, and 2018 to collect a valid sample of 47,949 individuals from 31 provinces. Our findings support the idea that cultural consumption has a significantly positive effect on subjective well-being and that internet use helps strengthen this relationship. Moreover, there is a “satiation point” where excessive cultural consumption may lead to a decrease in subjective well-being. In the case of excessive cultural consumption, cultural consumption leads to a more noticeable decrease in well-being. Our results hold after various robustness checks and after endogeneity concerns are addressed through instrumental variable methodology. Furthermore, heterogeneity analysis revealed that this effect is more pronounced in the elderly and female populations.